Solve for x (complex solution)
x=\frac{-\sqrt{39}i+11}{20}\approx 0.55-0.3122499i
x=\frac{11+\sqrt{39}i}{20}\approx 0.55+0.3122499i
Graph
Share
Copied to clipboard
11x-3-6x^{2}=4x^{2}+1
Use the distributive property to multiply 1-3x by 2x-3 and combine like terms.
11x-3-6x^{2}-4x^{2}=1
Subtract 4x^{2} from both sides.
11x-3-10x^{2}=1
Combine -6x^{2} and -4x^{2} to get -10x^{2}.
11x-3-10x^{2}-1=0
Subtract 1 from both sides.
11x-4-10x^{2}=0
Subtract 1 from -3 to get -4.
-10x^{2}+11x-4=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-11±\sqrt{11^{2}-4\left(-10\right)\left(-4\right)}}{2\left(-10\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -10 for a, 11 for b, and -4 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-11±\sqrt{121-4\left(-10\right)\left(-4\right)}}{2\left(-10\right)}
Square 11.
x=\frac{-11±\sqrt{121+40\left(-4\right)}}{2\left(-10\right)}
Multiply -4 times -10.
x=\frac{-11±\sqrt{121-160}}{2\left(-10\right)}
Multiply 40 times -4.
x=\frac{-11±\sqrt{-39}}{2\left(-10\right)}
Add 121 to -160.
x=\frac{-11±\sqrt{39}i}{2\left(-10\right)}
Take the square root of -39.
x=\frac{-11±\sqrt{39}i}{-20}
Multiply 2 times -10.
x=\frac{-11+\sqrt{39}i}{-20}
Now solve the equation x=\frac{-11±\sqrt{39}i}{-20} when ± is plus. Add -11 to i\sqrt{39}.
x=\frac{-\sqrt{39}i+11}{20}
Divide -11+i\sqrt{39} by -20.
x=\frac{-\sqrt{39}i-11}{-20}
Now solve the equation x=\frac{-11±\sqrt{39}i}{-20} when ± is minus. Subtract i\sqrt{39} from -11.
x=\frac{11+\sqrt{39}i}{20}
Divide -11-i\sqrt{39} by -20.
x=\frac{-\sqrt{39}i+11}{20} x=\frac{11+\sqrt{39}i}{20}
The equation is now solved.
11x-3-6x^{2}=4x^{2}+1
Use the distributive property to multiply 1-3x by 2x-3 and combine like terms.
11x-3-6x^{2}-4x^{2}=1
Subtract 4x^{2} from both sides.
11x-3-10x^{2}=1
Combine -6x^{2} and -4x^{2} to get -10x^{2}.
11x-10x^{2}=1+3
Add 3 to both sides.
11x-10x^{2}=4
Add 1 and 3 to get 4.
-10x^{2}+11x=4
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{-10x^{2}+11x}{-10}=\frac{4}{-10}
Divide both sides by -10.
x^{2}+\frac{11}{-10}x=\frac{4}{-10}
Dividing by -10 undoes the multiplication by -10.
x^{2}-\frac{11}{10}x=\frac{4}{-10}
Divide 11 by -10.
x^{2}-\frac{11}{10}x=-\frac{2}{5}
Reduce the fraction \frac{4}{-10} to lowest terms by extracting and canceling out 2.
x^{2}-\frac{11}{10}x+\left(-\frac{11}{20}\right)^{2}=-\frac{2}{5}+\left(-\frac{11}{20}\right)^{2}
Divide -\frac{11}{10}, the coefficient of the x term, by 2 to get -\frac{11}{20}. Then add the square of -\frac{11}{20} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-\frac{11}{10}x+\frac{121}{400}=-\frac{2}{5}+\frac{121}{400}
Square -\frac{11}{20} by squaring both the numerator and the denominator of the fraction.
x^{2}-\frac{11}{10}x+\frac{121}{400}=-\frac{39}{400}
Add -\frac{2}{5} to \frac{121}{400} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x-\frac{11}{20}\right)^{2}=-\frac{39}{400}
Factor x^{2}-\frac{11}{10}x+\frac{121}{400}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{11}{20}\right)^{2}}=\sqrt{-\frac{39}{400}}
Take the square root of both sides of the equation.
x-\frac{11}{20}=\frac{\sqrt{39}i}{20} x-\frac{11}{20}=-\frac{\sqrt{39}i}{20}
Simplify.
x=\frac{11+\sqrt{39}i}{20} x=\frac{-\sqrt{39}i+11}{20}
Add \frac{11}{20} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}